A VEDANTIC PERSPECTIVE OF ECOLOGY - Thottakara, Augustine (Journal of Dharma, 2001)
In this paper I intend to concentrate on one particular school of Hindu religion and philosophy, namely, the Srivaisnava religion, the philosophy of which is Visistadvaita, the Vedanta of qualified nondualism. The founder of this branch of Vedanta is Sri Ramanuja [10171137].